Comparative Evaluation of Serum Irisin Levels in Rheumatoid Arthritis and Multiple Sclerosis - Deniz, Gulnihal; Ercan, Zubeyde; Bilek, Furkan; Yentur, Songul Baglan; Alkan, Gokhan (Yuzuncu Yil Universitesi Tip Fakultesi, 2026)
Growing evidence indicates a close interaction between the autonomic nervous system and inflammatory processes. Irisin, a myokine primarily released from skeletal muscle, has recently been associated with immune regulation; however, data regarding its role in autoimmune diseases are limited. This study aimed to compare serum irisin levels in patients with rheumatoid arthritis (RA) and multiple sclerosis (MS) with those of healthy individuals. The study included 45 patients with RA, 45 patients with MS, and 45 age-and sex-matched healthy controls. Blood samples were obtained and serum irisin concentrations were measured using a commercially available enzyme-linked immunosorbent assay (ELISA) according to the manufacturer’s protocol. Patients were included under stable treatment conditions and low disease activity (DAS-28 <3.2 for RA; EDSS 2.0–5.0 for MS). Physical activity levels were not directly assessed and body composition parameters were not evaluated. Mean serum irisin levels were 246.11±119.6 pg/mL in RA, 1898.5±187.6 pg/mL in MS, and 93.87±68.50 pg/mL in controls (p=0.001). Compared with healthy controls, both RA and MS patients exhibited elevated serum irisin concentrations. Moreover, irisin levels were significantly higher in patients with M S than in those with RA (p=0.001). The findings suggest that increased serum irisin levels may be associated with autoimmune inflammatory conditions such as RA and MS. This elevation may be associated with inflammatory processes and could reflect a potenti al adaptive response. Further longitudinal and mechanistic studies are needed to clarify whether irisin primarily exerts anti-inflammatory or neuroprotective effects in autoimmune diseases. © 2026, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Autoimmune Diseases; Irisin; Multiple Sclerosis; Rheumatoid Arthritis